Efficient and Hole‐Transporting‐Layer‐Free CsPbI2Br Planar Heterojunction Perovskite Solar Cells through Rubidium Passivation. Issue 5 (13th February 2019) - Guo, Yixin; Zhao, Fei; Tao, Jiahua; Jiang, Jinchun; Zhang, Jungang; Yang, Jianping; Hu, Zhigao; Chu, Junhao
Abstract: Recently, inorganic perovskite CsPbI2 Br has gained much attention for photovoltaic applications owing to its excellent thermal stability. However, low device performance and high open‐voltage loss, which are the result of its intrinsic trap states, are hindering its progress. Herein, planar CsPbI2 Br solar cells with enhanced performance and stability were demonstrated by incorporating rubidium (Rb) cations. The Rb‐doped CsPbI2 Br film exhibited excellent crystallinity, pinhole‐free surface morphology, and enhanced optical absorbance. By using low‐cost carbon electrodes to replace the organic hole‐transportation layer and metal electrode, an excellent efficiency of 12 % was achieved with a stabilized efficiency of over 11 % owing to the suppressed trap states and recombination in the CsPbI2 Br film. Additionally, the annealing temperature for the Rb‐doped CsPbI2 Br film could be as low as 150 °C with a comparable high efficiency over 11 %, which is one of the best efficiencies reported for hole‐transporting‐layer‐free all‐inorganic perovskite solar cells. These results could provide new opportunities for high‐performance and stable inorganic CsPbI2 Br solar cells by employing A‐site cation substitution. Abstract : Defect passivation : All‐inorganic carbon‐based perovskite solar cells (PSCs), with Rb‐doped CsPbI2 Br as the absorber layer, exhibit improved efficiency and enhanced stability compared with PSCs with pristine CsPbI2 Br owing to the effectiveness of Rb incorporation in passivating defects states.